2014
DOI: 10.1080/14786419.2014.983921
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a new triterpene derivative andin vitroandin vivoanticancer activity of ethanolic extract from root bark ofZizyphus nummulariaAubrev

Abstract: The various parts of Zizyphus nummularia has been used traditionally in several disease conditions. However, its anticancer activity and mechanism of action remain to be elucidated. Considering this, the objective of this study was to isolate, identify and screen for possible anticancer activity in vitro and in vivo of the ethanolic extract (EE) and isolated identified compound (IC) from Z. nummularia root bark. The in vitro activity against human breast cancer, leukaemia, ovarian cancer, colon adenocarcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…In our study, we showed that ZNE attenuated the proliferation of Capan-2. This is in line with the cytotoxic effect of Z. nummularia on five cancer cell lines: human breast cancer (MCF-7), leukemia (K-562), ovarian cancer (OVCAR-3), human colon adenocarcinoma (HT-29), and human kidney carcinoma (A-498) [ 13 ]. However, this effect was not imparted by Z. nummularia leaf extract but rather by a compound isolated from Z. nummularia root barks [ 13 ].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In our study, we showed that ZNE attenuated the proliferation of Capan-2. This is in line with the cytotoxic effect of Z. nummularia on five cancer cell lines: human breast cancer (MCF-7), leukemia (K-562), ovarian cancer (OVCAR-3), human colon adenocarcinoma (HT-29), and human kidney carcinoma (A-498) [ 13 ]. However, this effect was not imparted by Z. nummularia leaf extract but rather by a compound isolated from Z. nummularia root barks [ 13 ].…”
Section: Discussionsupporting
confidence: 68%
“…Since it is bountiful in bioactive molecules such as tannins, flavonoids, steroids, glycosides, and alkaloids, Ziziphus nummularia has been used to treat a wide spectrum of pathological conditions including cold, diarrhea, anemia, bronchitis, indigestion, and inflammation [ 12 ]. In addition, its extracts are well known to inhibit the malignant phenotype of several cancer types, such as human breast cancer (MCF-7), leukemia (K-562), ovarian cancer (OVCAR-3), human colon adenocarcinoma (HT-29), and human kidney carcinoma (A-498) [ 13 , 14 ]. In vivo, a chemical extracted from Z. nummularia decreased the tumor volume of Ehrlich ascites carcinoma-bearing mice, and more importantly, it increased their survival [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely used in folk medicine of various countries (Iran, India, Pakistan, and others) as a treatment for a wide spectrum of ailments such as cold, cough, throat inflammation, and diabetes as well as a sedative, aphrodisiac, and an antiseptic [25, 26]. A recent study identified a new terpene isolated from Z. nummularia that appears to possess potent anticancer activity, both in vitro and in vivo [26]. Relevantly, the leaves of Z. nummularia have been recently shown to elicit an anti-inflammatory effect [6].…”
Section: Discussionmentioning
confidence: 99%
“…Also a derivative of picene, namely octadecahydro-picene-2,3,14,15-tetranone isolated and purified from the root bark of Zizyphus nummularia, reported to possess anti-cancer and anti-inflammatory activities. 9,10 Many polycyclic aromatic compounds such as flavone, quercetin, chrysin and pyrimido [4,5-b]quinolines were reported to possess anti-inflammatory or antioxidant properties. 11,12 Because of the close structural similarity with the reported polycyclic compounds, we have envisaged to explore the anti-inflammatory activity of picene analogues.…”
Section: Introductionmentioning
confidence: 99%